The risk of recurrent stroke at 24 months in patients with symptomatic carotid near‐occlusion: results from CAOS, a multicentre registry study. (17th June 2019) - García‐Pastor, A.; Gil-Núñez, A.; Ramírez‐Moreno, J. M.; González‐Nafría, N.; Tejada, J.; Moniche, F.; Portilla‐Cuenca, J. C.; Martínez‐Sánchez, P.; Fuentes, B.; Gamero‐García, M. Á.; Alonso de Leciñana, M.; Masjuán, J.; et al.
Abstract : Background and purpose: The risk of recurrent stroke amongst patients with symptomatic carotid near‐occlusion (SCNO) has not been clearly established, and its management remains controversial. The aim was to define the 24‐month risk of recurrent stroke and to analyse the effect of the different treatment modalities (medical treatment and revascularization) in a population of patients with SCNO. Methods: A multicentre, nationwide, prospective study from January 2010 to May 2016 was performed. Patients with angiography‐confirmed SCNO were included. The primary end‐point was ipsilateral ischaemic stroke including periprocedural events within 24 months following the presenting event. Revascularization results and periprocedural complications, ipsilateral transient ischaemic attack, disabling or fatal stroke, and mortality were also noted. Results: The study population comprised 141 patients from 17 Spanish centres. Seventy patients (49.6%) were treated by revascularization (carotid stenting in 47, endarterectomy in 23). Complete revascularization was achieved in 58 patients (83%). Periprocedural stroke or death occurred in 5.7%. The 24‐month cumulative incidence of the primary end‐point was 11.1% (95% confidence interval 5.8–16.4; n = 15), 12% in the medical treatment group and 10.2% in the revascularization group, log‐rank P = 0.817. The cumulative rates of ipsilateral ischaemic stroke or transient ischaemic attack, disabling or fatal stroke, and mortality, were 17%, 4.5% and 7.5%, respectively. Conclusions: The rate of ipsilateral ischaemic stroke in patients with SCNO seems to be lower than the known rate associated with severe carotid stenosis without near‐occlusion. The potential benefit of revascularization in the prevention of stroke in patients with SCNO may be influenced by the effectiveness and safety of the procedure.